2018
DOI: 10.3390/ijms19113689
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Weightlessness, Isoproterenol, and Radiation on DNA Damage Response and Cytokine Production in Immune Cells

Abstract: The implementation of rotating-wall vessels (RWVs) for studying the effect of lack of gravity has attracted attention, especially in the fields of stem cells, tissue regeneration, and cancer research. Immune cells incubated in RWVs exhibit several features of immunosuppression including impaired leukocyte proliferation, cytokine responses, and antibody production. Interestingly, stress hormones influence cellular immune pathways affected by microgravity, such as cell proliferation, apoptosis, DNA repair, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…Currently, NASA's most advanced GCR simulators provides some insight into the effect of GCR on biological systems [70]. A recent study by Moreno-Villanueva and colleagues examined the combined and individual effects of γ-radiation (radiation source undefined), simulated microgravity and physiological stress on isolated, unstimulated, peripheral blood mononuclear cells [29]. They concluded that radiation significantly influenced cytokine secretion but only under simulated microgravity conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, NASA's most advanced GCR simulators provides some insight into the effect of GCR on biological systems [70]. A recent study by Moreno-Villanueva and colleagues examined the combined and individual effects of γ-radiation (radiation source undefined), simulated microgravity and physiological stress on isolated, unstimulated, peripheral blood mononuclear cells [29]. They concluded that radiation significantly influenced cytokine secretion but only under simulated microgravity conditions.…”
Section: Discussionmentioning
confidence: 99%
“…An important objective for future experiments is to take the additional layers of spaceflight complexity into consideration by mimicking the synergistic effect of multiple space stressors in a ground-based experiment, as outlined by Moreno-Villanueva et al [29]. In addition, the future goal should also include in vivo experiments with neutrons and other high-LET radiation qualities relevant to the space radiation environment, with special emphasis for spaceflight-relevant low dose rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations